1997
DOI: 10.1093/emboj/16.13.3898
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic processing regulates receptor specificity and activity of VEGF-C

Abstract: The recently identified vascular endothelial growth factor C (VEGF-C) belongs to the platelet-derived growth factor (PDGF)/VEGF family of growth factors and is a ligand for the endothelial-specific receptor tyrosine kinases VEGFR-3 and VEGFR-2. The VEGF homology domain spans only about one-third of the cysteine-rich VEGF-C precursor. Here we have analysed the role of post-translational processing in VEGF-C secretion and function, as well as the structure of the mature VEGF-C. The stepwise proteolytic processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
639
1
14

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 678 publications
(674 citation statements)
references
References 50 publications
20
639
1
14
Order By: Relevance
“…We found that VEGF-C downregulation was accompanied by reappearance of certain traits of epithelial phenotype and a decrease in expression of mesenchymal markers that was observed in both A549 ( Figure 6) and HCT116 cells (Supplementary Immature forms of VEGF-C bind only to VEGFR3; mature form binds to VEGFR3 with higher affinity than immature forms, and additionally interacts with VEGFR2 (Joukov et al, 1997). a-tubulin protein was analyzed as loading control.…”
Section: Resultsmentioning
confidence: 87%
“…We found that VEGF-C downregulation was accompanied by reappearance of certain traits of epithelial phenotype and a decrease in expression of mesenchymal markers that was observed in both A549 ( Figure 6) and HCT116 cells (Supplementary Immature forms of VEGF-C bind only to VEGFR3; mature form binds to VEGFR3 with higher affinity than immature forms, and additionally interacts with VEGFR2 (Joukov et al, 1997). a-tubulin protein was analyzed as loading control.…”
Section: Resultsmentioning
confidence: 87%
“…Subsequently, the propeptides can be proteolytically removed to generate mature forms consisting of VHD dimers. The full-length forms of both growth factors bind the lymphangiogenic receptor VEGFR-3 but the mature forms do so with greater affinity (Joukov et al, 1997;Stacker et al, 1999), suggesting that the degree of proteolytic processing of VEGF-C and VEGF-D may in part determine the extent of lymphangiogenesis induced by these proteins in a tumour. Once VEGF-C is processed to the mature form it acquires the capacity to bind VEGFR-2 (Joukov et al, 1997), a cell surface receptor tyrosine kinase thought to signal for angiogenesis.…”
Section: Mechanisms Of Lymphangiogenic Signallingmentioning
confidence: 99%
“…The full-length forms of both growth factors bind the lymphangiogenic receptor VEGFR-3 but the mature forms do so with greater affinity (Joukov et al, 1997;Stacker et al, 1999), suggesting that the degree of proteolytic processing of VEGF-C and VEGF-D may in part determine the extent of lymphangiogenesis induced by these proteins in a tumour. Once VEGF-C is processed to the mature form it acquires the capacity to bind VEGFR-2 (Joukov et al, 1997), a cell surface receptor tyrosine kinase thought to signal for angiogenesis. In the case of VEGF-D, the affinity for VEGFR-2 is increased approximately 290-fold by proteolytic conversion of the full-length to the mature form (Stacker et al, 1999).…”
Section: Mechanisms Of Lymphangiogenic Signallingmentioning
confidence: 99%
“…In vitro studies have shown that VEGF-C and VEGF-D exhibit mitogenic effects for vascular and lymphatic endothelial cells and survival-promoting abilities for lymphatic endothelial cells through VEGFR3 Achen et al, 1998;Marconcini et al, 1999;Veikkola et al, 2001). Both growth factors promote angiogenesis in in vitro assays (Joukov et al, 1996;Joukov et al, 1997;Marconcini et al, 1999). Vascular endothelial growth factor-C promotes the formation of capillary-tube structures by lymphatic endothelial cells, but not blood vascular endothelial cells, in a collagen sandwich assay (Podgrabinska et al, 2002).…”
Section: Roles Of Vegf-c and Vegf-dmentioning
confidence: 99%